Directly and Continuously Hydration of Higher Olefins to Higher Alcohols over an Amphiphilic Hollow HZSM-5 Zeolite Catalyst - Lin, Zhikuan (Langmuir : the ACS journal of surfaces and colloids, 2025)
Higher-alcohol synthesis from directly higher olefin hydration technology shows great potential for their industrial production, yet it faces challenges including thermodynamic limitations and catalyst stability. This study develops an amphiphilic hollow HZSM-5 (A-H-HZSM-5) through a two-step modification: creating hollow structures via mixed-alkali (TPAOH/Na2CO3) treatment, followed by octyltrimethoxysilane (OTS) grafting for amphiphilicity. The reaction performances of 1-octene hydration to octanol over the prepared catalysts as a model reaction are investigated. Characterization shows mixed-alkali treatment introduces meso/macropores, increasing the pore volume by 3.6 times to form hierarchical pores for improved mass transfer. OTS grafting creates a hydrophobic surface layer, boosting the water contact angle to 147.25° for amphiphilic balance. Alkali treatment reduces strong Bro̷nsted acids, while the OTS modifies acid accessibility. The synergy of the hollow structure and amphiphilicity optimizes mass transfer and adsorption equilibrium, enhancing catalytic performance in olefin hydration. In 1-octene hydration tests under optimized conditions (200 °C, 1.0 MPa, 2 h-1, water/olefin = 10:1), A-H-HZSM-5 achieves 1.37% conversion with 85.03% alcohol selectivity. Systematic investigation reveals that the OTS loading critically regulates surface hydrophobicity, which improves the phase contact upon the surface acid sites of catalysts, while reaction parameters (temperature, pressure, and water ratio) synergistically achieve the thermodynamic equilibrium. This work demonstrates the dual optimization of adsorption and mass transfer through architectural engineering, offering guidance for designing amphiphilic catalysts in hydration reaction systems